PITUICYTOMA; BENIGN SPINDLE CELL TUMOR OF POSTERIOR PITUITARY GLAND: A CASE REPORT - Hungspreug; Phudhichareonrat; Leum-udom, AND (The ASEAN Journal of Radiology, 2023)
Pituicytoma is one of the rare benign primary tumors of the posterior pituitary gland, originated from intrinsic special glial cells of the gland. The previous nomenclature of posterior pituitary tumors has been confusing with pituicytoma. "Pituicytoma" should be neurohypophyseal astrocytoma only. Clinical and laboratory presentations as well as neuroimaging are not specific; the correct diagnoses are achieved only after histopathological examinations. This article revealed a clinical presentation, neuroimaging findings and pathological features ofa large sellar/suprasellar tumor in a 46-year-old male, having diagnosed of pituicytoma.